An Analysis of Skimming and Scanning Strategies in Teaching Reading Skill Used by the English Teacher at the Eighth Grade of UPTD SMP Negeri 1 Mandrehe Barat - Herni Berkat Gulo; Yaredi Waruwu; Riswan Zega; Kristof Martin Efori Telaumbanua (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to examine the use of skimming and scanning techniques in reading instruction implemented by the English teacher for eighth-grade students at UPTD SMP Negeri 1 Mandrehe Barat. The research focuses on how these techniques are applied during classroom activities and explores the challenges faced by the teacher in the teaching process. A qualitative descriptive approach was employed, with data collected through classroom observations, teacher interviews, and supporting documentation. The findings reveal that the teacher was able to apply skimming and scanning effectively to improve students’ reading comprehension. Skimming enabled students to identify the main ideas, themes, and general meaning of the text, while scanning facilitated the ability to locate specific information such as names, dates, and key terms. These techniques not only improved reading speed but also encouraged more active participation among students, creating a more interactive learning atmosphere. However, the study also identified several obstacles, including limited instructional time, variations in students’ reading proficiency levels, and challenges related to inadequate vocabulary mastery, which sometimes hindered comprehension. Despite these challenges, the integration of skimming and scanning proved beneficial in motivating students to read more purposefully and strategically. The study concludes that these reading strategies play a vital role in enhancing comprehension and engagement in English language learning. It is recommended that teachers receive further professional development and be supported with appropriate teaching resources to optimize the application of skimming and scanning techniques in various classroom contexts.